A Training of Organic Fertilizer Preparation from Wasted Rice Straw in Rice Caltivation Area-Nagari Dilam, Bukit Sundi District, Solok Regency - Okta Suryani (Pelita Eksakta, 2022)
Abstract – Rice is one of the national mainstay commodities that have an important role in the Indonesian economy, which is also a mainstay crop commodity in Solok Regency. Solok Regency is famous for its high quality rice. Nagari Dilam, Bukit Sundi District, as a village with a large rice commodity in Solok Regency, most of the residents have a livelihood as rice farmers. To obtain good yields, the material that is needed during the planting process is fertilizer. However, fertilizer problems almost always appear every year in this area. In the last 2 years, farmers have complained due to these problems, including the price of commercial inorganic fertilizers (Urea, SP36, KCl, ZA) which tends to increase. In addition, without realizing it, the intensive use of commercial inorganic fertilizers can cause a decrease in soil fertility and soil organic matter decreases. The idea of using wasted straw came up as a way to solve these problem to prodice orgnic fertilizer. A training in preparation of organic fertilizer from wasted straw has been conducted in Nagari Dilam. The produced organic fertilizer has been characterized for N, P,K containing subtance. The fertilizer contains 0.030%, 4.563% and 1.369% of N, P, and K respectively. Keywords Organic, Fertilizer, Wasted Straw, Rice